The association between lower prognostic nutritional index and higher short- & long-term mortality in older adults (≥ 70 years) undergoing coronary artery bypass grafting: a retrospective study - Zihua Liu; Zikun Wang; Qi Huang; Bo Hu; Mingliang Li; Yilin Pan; Yangyang Sun; Hao Cao; Kai Xu; Lei Yang; Zhi Li; Yangyang Zhang; et al. (BMC Geriatrics)
Abstract Background The incidence of cardiovascular diseases among old individuals is on the rise with the growing trend of population aging. Coronary artery bypass grafting (CABG) is an important treatment modality for coronary heart diseases and is increasingly employed in older adults. However, concerns arise due to the poor prognosis following surgery in this population. The prognostic nutritional index (PNI) reflects the nutritional status and immune function of patients. It has been previously utilized in prognostic assessments for other surgical procedures and receives increasing attention in the field of cardiovascular surgery. Methods This retrospective study examined a cohort of older adults (70 to 90 years) who underwent initial CABG-only surgery at five cardiac centers, excluding patients with coexisting neoplastic or immune disorders. The objective was to investigate the relationship between low PNI and both short- and long-term mortality in this population. PNI was calculated based on total lymphocyte count and serum albumin concentration measured before surgery, after surgery, and before discharge. The cut-off value of PNI was established through receiver’s operating characteristic curve. Univariate and multivariate logistic and cox regression analyses were performed to identify the independent risk factors related to the occurrence of short- and long-term mortality. Smooth survival model and Kaplan-Meier analysis were employed to evaluate survival and relative risk. Results Among the 1173 patients, 90 patients (7.7%) experienced short-term mortality and 131 (11.2%) patients had long-term mortality during follow-up and the survival probabilities at 1,3,5,10 years were 96.98%, 94.64%, 89.89%, 76.96%, respectively. In this population, lower preoperative PNI was independently and significantly correlated with short-term mortality (OR = 2.372, 95%CI: 1.394–4.035). Additionally, a low PNI before discharge was independently and significantly associated with increased long-term mortality risk in older adults who underwent CABG (HR = 1.451, 95%CI: 1.012–2.082). Long-term follow-up also showed that patients with a low PNI before discharge had significantly higher long-term mortality (log-rank: P = 0.004). Moreover, extended Kaplan-Meier analysis showed that women (log-rank: P = 0.005) and obese patients (log-rank: P = 0.073) appeared to have higher long-term survival rates. Conclusion The current investigation unveiled that PNI has emerged as an autonomous determinant for both short-and long-term mortality in older adults receiving CABG.